Infodemiology on vaccination on the Brazilian internet: analysis of technical quality criteria (Research, Society and Development, 2022)
This study aimed to locate and analyze, based on quality criteria, news websites that presented information about vaccines. This is a descriptive, observational and cross-sectional infodemiological study, in which the technical quality characteristics of Brazilian websites on the topic of vaccination were analyzed. The search was carried out from October to December 2021, including pages in Portuguese. For the evaluation of technical quality criteria, an instrument composed of sixteen closed questions was used, which address the analysis of reliability and information. 20,800,000 news websites were identified, after applying the exclusion criteria, 139 pages were analyzed. None of the pages declared conflicts of interest. Only 56.1% of the pages revealed the author's name and 16.5% did not cite the references used. Only 10.8% of the news presented the degrees of clinical evidence. The analysis carried out alerts to a concern in the quality and dissemination of information related to vaccination, which must be considered for the national repercussion and, also, for the fight against Fake News.